Efektivitas Penambahan Latihan Penguatan Otot Ekspirasi pada Senam Lansia terhadap Kebugaran Kardiorespirasi Lansia Pre-Frail - Hakim, Ratih Dwiratna; Indriastuti, Lanny; Setiawati, Erna (Majalah Kedokteran Indonesia, 2025)
Introduction: The aging process will cause anatomical and physiological changes in various organs and the body systems, including changes in the cardiovascular, respiratory, and musculoskeletal systems which then progressively reduce cardiovascular and pulmonary functional capacity, ultimately affecting cardiorespiratory fitness, which can be assessed by a 6-minute walk test/6MWT. Aerobic exercise, including senam lansia, will affect cardiorespiratory fitness by increasing muscles blood flow. Adding expiratory muscle strengthening exercises with a Positive Expiratory Pressure/PEP threshold will strengthen expiratory muscles, the most common muscles affected in aging. This study aims to prove the effectiveness of adding expiratory muscle-strengthening exercises to senam lansia on the cardiorespiratory fitness of the pre-frail elderly. Method: 24 subjects who met the study criteria were randomly divided into an intervention group (n=12) who receive PEP 5 times per week + senam lansia 3 times per week for 6 weeks, and a control group (n=12) who only had senam lansia 3 times per week for 6 weeks. Cardiorespiratory fitness was measured before and after intervention using the 6MWT. Result: There was an increase in 6MWT scores before and after treatment in both the intervention group (p=0.002) and the control group (p<0.001). Comparison between groups showed a significant 6MWT score difference in the intervention group (p<0.001). Conclusion: The addition of expiratory muscle strengthening exercises to senam lansia for 6 weeks had a better improvement in cardiorespiratory fitness compared to only having senam lansia.